Legal Analysis of Copyright Evidence for Song Covers - Indra Pratama Putra; Dudung Hidayat; Raden Handiriono (Riviera Publishing, 2026)
This study aims to evaluate the role and weight of evidence in copyright disputes related to song cover practices in Indonesia. The background of this research focuses on the increasing use of songs by third parties without permission from the creator, particularly through digital platforms, which has the potential to cause violations of economic rights. The issues examined include legal sanctions for copyright infringement in song cover practices and the role of evidence at the evidentiary stage. The research method used is normative legal analysis with statutory and conceptual approaches. The findings show that the use of songs in cover versions without permission may be subject to civil sanctions in the form of damages and criminal sanctions in accordance with the Copyright Law. In addition, evidence such as copyright registration certificates, work recordings, contract documents, and testimony from witnesses and experts plays an important role in proving copyright ownership. In conclusion, although copyright is declarative, the existence of evidence remains a crucial factor in determining the success of law enforcement and the resolution of copyright disputes in song cover practices